Keys for Isolation suborders and Families and genera and species of Book and Bark lice in Baghdad and Babylon [Order PSOCOPTERA] - Baghdad Science Journal (مجلة بغداد للعلوم, 2017)
A taxonomic keys was established of book and bark lice Order Psocoptera to isolated insects in Iraq from different localities of Baghdad and Babylon provinces. Thirteen species belong to eight genera and five families have been studied and described in details, these species were recorded for the first time in Iraq. These species are: Belaphopsocus badonneli New, 1971; Belaphotroctes oculeris Bodonnel, 1973; Embodopsocosis newi Bodonnel, 1973; Epipsocus stigamaticus Mockeord, 1991; Lepinotus huoni Schmidt and New, 2008; Liposcelies decolor Peramane 1925 Liposcelies paeta Pearman 1942 Liposclies bostrychphila Badonnel 1931; Liposclies brunnea Mostchulsky 1852; Liposclies entoophila Enderlein 1907; Neopsocopsis minuscule Li 2002 ; Nonapsocus oceanicus Pearman 1928.; Identification key to suborders, families, genera and species were designed according to differences of morphological characters. Adults were described in details and all body parts were pictured and some of them drawn by Camera Lucid